1962
DOI: 10.1366/000370262774416010
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrochemical Determination of Trace Impurities in Graphite

Abstract: Optical emission spectrographic procedures are described for the estimation of some 60 elements in graphite. Using sodium fluoride as a carrier, the dc arc is employed for a direct examination of powdered graphite, while the copper spark method is used for analysis of the residue after ashing the sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…8-Quino-linol was used for the spectrophotometric determination of vanadium by Awasthi and Khasgiwale (17) who measured the absorbance in a chloroform solution at 550 µ and by Magee and Witwit (171) who measured the absorbance in the infrared region at 10.50 microns. Pearse ( 218 113); V (196); Eu203 (240); alkali metals (274); graphite (99); ores, rocks, minerals (126, 271, 277); natural materials (191) Zt (200); Eu203 (240); ores, rocks, minerals (258, 271); natural materials (191) Study of conditions and/or interferences (29); Cr (113); Ta (154, 202)', A1203 or Sn02 (211); U02 (32); graphite (8, 99); rocks and minerals (126); soils and plants (50); polyphenyls (106) Mo (249); Ta (202); Nb-Ta (197); alkali metals (274); rocks and ores (231,271) Mo (249); Pu (141); Nb-Ta (197); alkali metals (274); rocks and ores (231,271) Study of conditions and/or interferences (265); Bi (144); Ta (154,202); Nb (153); Np (283); V (196); Mo (66); Eu203 (240); U02 (32); A1203 and Sn02 (211); graphite (99); ruby and sapphire (56); soils and plants (50); rocks and minerals (126); polyphenyls (106) Cr (113); Ta (202); alkali metals (274); CO2 (32); Eu203 (240); graphite (99); rocks (76); plant tissue (50, 62); polyphenyls (106) Study of conditions and/or interferences (265); Ta (202); alkali metals (274); U02 (32); graphite (99) dinm with sodium metavanadate…”
Section: Vanadiummentioning
confidence: 99%
See 1 more Smart Citation
“…8-Quino-linol was used for the spectrophotometric determination of vanadium by Awasthi and Khasgiwale (17) who measured the absorbance in a chloroform solution at 550 µ and by Magee and Witwit (171) who measured the absorbance in the infrared region at 10.50 microns. Pearse ( 218 113); V (196); Eu203 (240); alkali metals (274); graphite (99); ores, rocks, minerals (126, 271, 277); natural materials (191) Zt (200); Eu203 (240); ores, rocks, minerals (258, 271); natural materials (191) Study of conditions and/or interferences (29); Cr (113); Ta (154, 202)', A1203 or Sn02 (211); U02 (32); graphite (8, 99); rocks and minerals (126); soils and plants (50); polyphenyls (106) Mo (249); Ta (202); Nb-Ta (197); alkali metals (274); rocks and ores (231,271) Mo (249); Pu (141); Nb-Ta (197); alkali metals (274); rocks and ores (231,271) Study of conditions and/or interferences (265); Bi (144); Ta (154,202); Nb (153); Np (283); V (196); Mo (66); Eu203 (240); U02 (32); A1203 and Sn02 (211); graphite (99); ruby and sapphire (56); soils and plants (50); rocks and minerals (126); polyphenyls (106) Cr (113); Ta (202); alkali metals (274); CO2 (32); Eu203 (240); graphite (99); rocks (76); plant tissue (50, 62); polyphenyls (106) Study of conditions and/or interferences (265); Ta (202); alkali metals (274); U02 (32); graphite (99) dinm with sodium metavanadate…”
Section: Vanadiummentioning
confidence: 99%
“…Heffelfinger et al ( 113) determined molybdenum and other impurities in high-purity chromium by first volatilizing the chromium as chromyl chloride and then examining the remaining solution spectrographically. Goleb, Faris, and Meng (99) determined a number of elements including molybdenum in graphite by the copper spark method after first ashing the sample. Molybdenum was spectrographically determined by Edge, Dunn, and Ahrens (76) in granitic and related rocks after first concentrating it along with iron by extracting them into tri-n-butylphosphate.…”
Section: Chromiummentioning
confidence: 99%
“…32,33 Only a few studies were found in the literature regarding the determination of REE in graphite, probably due to the difficulty of graphite digestion and the problems related to the determination step. In these studies, 34,35 graphite digestion was performed by dry ashing and a spectrographic method was used for REE determination. The limits of detection were relatively high (in the range of mg g À1 ) and a long time was required for sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Those that could be mentioned are hollow-cathode sputtering (26)(27)(28)(29), the spark-in-spray approach (30), the King furnace method (31), a scheme which utilizes a discharge tube (32), and a capacitor discharge lamp method (33). A flame was used throughout this work.…”
mentioning
confidence: 99%